2023
DOI: 10.1111/ddg.15134
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative pain management in dermatosurgery – current practice in Germany: Data analysis of a Germany‐wide online survey among dermatosurgeons

Abstract: SummaryBackgroundAdequate pain management should be part of the standard of care in surgical procedures. However, there is a paucity of data in the field of dermatosurgery. In a standardized online survey among dermatosurgeons working in Germany, the current practice of perioperative pain management was investigated.MethodsMembers of the German Society for Dermatosurgery (DGDC) and heads of dermatosurgical departments were asked to participate. Questions were related to practical implementation of perioperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Pain should be regularly assessed perioperatively to ensure adequate analgesia. However, our survey of dermatologic surgeons found that only a quarter of respondents performed a standardized pain assessment 21 . Simple rating scales (e.g., the Numerical Rating Scale [NRS] with a classification of pain intensity from 0 = no pain to 10 = worst pain imaginable) are best suited for assessing pain intensity 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain should be regularly assessed perioperatively to ensure adequate analgesia. However, our survey of dermatologic surgeons found that only a quarter of respondents performed a standardized pain assessment 21 . Simple rating scales (e.g., the Numerical Rating Scale [NRS] with a classification of pain intensity from 0 = no pain to 10 = worst pain imaginable) are best suited for assessing pain intensity 1 .…”
Section: Discussionmentioning
confidence: 99%
“…There are no guidelines for postoperative pain management after dermatologic surgery in Germany. In most cases, patients are treated on the experience of doctors or clinical in‐house standards 21 . International evidence shows that treatment with non‐opioid analgesics is often sufficient after dermatologic surgery under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation